Voices Appeared: Carl Theodor Dreyer’s La Passion de Jeanne d’Arc and early fifteenth-century music: live music, silent film and vocal performance practices - Greig, Donald (2019)
This thesis considers its material from both a historical-critical and a performative-creative standpoint. It brings together complementary approaches: historical research, knowledge of musical repertoires, performance studies and creative practice, and film-music studies. It addresses questions of silent cinema, of music and narrative, of music and image, of live musical performance and early fifteenth-century history in the context of a large-scale creative project, Voices Appeared. This project and the critical approach of the thesis are based on first-hand engagement with the 1928 Carl Theodor Dreyer silent film, La Passion de Jeanne d’Arc and with the polyphonic music performed and composed during Jeanne d’Arc’s lifetime (c. 1412–1431). It suggests new perspectives for the understanding and critical reception of the musical and cinematic aspects of the creative project, and of the film itself. It also examines the use of music in Dreyer’s later sound films and various alternative soundtracks for La Passion de Jeanne d’Arc, setting all this in a wider relation to Dreyer’s practice and oeuvre.